STUDENTS' LITERACY CULTURE IN NON DIGITAL TECHNOLOGY AREA (PESANTREN) - Elda Yulia Ryandini; Devi Puspitasari (ETERNAL (English, Teaching, Learning and Research Journal), 2021)
Literacy is a social practice. In the past, literacy was only focused on reading and writing. Recently, literacy can happen everywhere, become a culture and people can make meaning of the practice. Literacy also cannot be separated from technology nowadays. Most people become digital natives to accomplish their daily business in which it is also the literacy activities. This study wants to clarify students’ preference in reading, to know students’ multimodal literacy, to probe students’ literacy practice in Pesantren, and to probe students’ literacy cultures if there are some digital technology stuffs. By applying qualitative approach using questionnaires and semi-structured interview to students, the results showed that mostly students were not really love reading (medium) in Pesantren because of no any book collections, the obligation of their own regulation to finish what they have read, boredom reading, no much time to read due to some other activities in Pesantren and preference to sleep rather than to read in Pesantren. Students also preferred reading novel as their multimodal literacy in Pesantren. The following answers, students conveyed that they felt so-so after doing literacy practice. The last, the answers related to the literacy culture if they meet some digital technology stuffs were various. Most students would not read at all at home when they get holiday. Most students also were very agreed if they have access to digital technology stuffs in Pesantren, but the claims also showed that the presence of digital technology stuffs would disturb their reading quality. Therefore, the students’ literacy cultures in non-digital technology area are average because they have various main activities of Pesantren to do and the availability of the access to some digital technology stuffs in Pesantren are seen disturbing.